2020
DOI: 10.1037/cpp0000299
|View full text |Cite
|
Sign up to set email alerts
|

PTSS in fathers of VLBW infants two to four years postpartum: A pilot study.

Abstract: Aim:To conduct a pilot study to compare fathers of very low birth weight (VLBW; <1500grams) infants and of term infants at two to four years postpartum for self-reported post-traumatic stress symptoms (PTSS) related to the previous birth of their baby, and for depression, and anxiety. The prevalence of paternal PTSS was compared with that of a historical cohort of mothers of VLBW infants followed up at a similar postnatal age.Methods: 26 fathers of VLBW infants and 22 fathers of term infants completed four val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Furthermore, perceived social support 4-6 weeks postpartum showed a negative bivariate association with PTSS 5 years later for both parents, but the association turned insignificant in multiple regression analysis. This result was unexpected since previous research has shown a close connection between low social support and PTSS from some weeks up to 2 years after birth (6,12,17). One explanation for this result might be that lack of social support played an important role for the development of PTSS after birth, as for mothers, a positive moderate sized bivariate association was found between these two variables.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Furthermore, perceived social support 4-6 weeks postpartum showed a negative bivariate association with PTSS 5 years later for both parents, but the association turned insignificant in multiple regression analysis. This result was unexpected since previous research has shown a close connection between low social support and PTSS from some weeks up to 2 years after birth (6,12,17). One explanation for this result might be that lack of social support played an important role for the development of PTSS after birth, as for mothers, a positive moderate sized bivariate association was found between these two variables.…”
Section: Discussionmentioning
confidence: 63%
“…Mehler et al (9) described a decrease of PTSS in fathers of low-risk preterm infants from birth to 3 months postpartum. Alexander et al (17) reported elevated PTSS in 27% of fathers of preterm infants 2-4 years after birth using the IES-R. However, since this was a small cross-sectional study, conclusions about the long-term course of PTSS cannot be drawn.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Preterm birth is associated with increased anxiety, post-natal depression (PND) and post-traumatic stress symptoms (PTSS) in both mothers Open access and fathers; symptoms persist even at 2-4 years postpartum. [26][27][28] The additional impact of the COVID-19 pandemic and adding to their burden through restrictive visiting policies would seem only likely to increase the risk of PND and PTSS and disruption of parental-infant bonding. 16 19 There are a few study limitations.…”
Section: Open Accessmentioning
confidence: 99%